Serum Biochemical Responses to Nigella sativa Seed Powder Supplementation in Chickens Experimentally Infected with Very Virulent Infectious Bursal Disease Virus: Serum Biochemical Responses due to Nigella sativa in vvIBDV-Challenged Chickens - Muhammed Shuaib Muhammed; Ochuko Orakpoghenor; Sunday Blessing Oladele; Bisalla Mohammed; Ibrahim Waziri Musa (Jurnal Agro Veteriner, 2026)
Nigella sativa possesses immunomodulatory and antiviral properties, but its effects during infectious bursal disease virus (IBDV) infection remain unclear. This study evaluated the impact of N. sativa seed powder (NSSP) supplementation on serum biochemical indices of cockerels challenged with very virulent IBDV (vvIBDV). One hundred Dominant Black Marshal birds were divided into five groups (A–E): Groups A and B received a basal diet, C and D received 2.8 g/kg NSSP from 21–27 days of age (doa), and E received NSSP continuously from 1–42 doa. On day 28, Groups B, D, and E were orally challenged with vvIBDV. Serum collected from days 1–42 was analyzed for total protein, albumin, globulin, urea, and creatinine. Results revealed that Group E had significantly (p < 0.05) higher total protein (from 31 doa) and globulin (from 32 doa) up to 42 doa compared to other groups. The albumin/globulin ratio was significantly lower (p < 0.05) in Group E from 31–42 doa, while serum albumin, urea, and creatinine showed no significant differences. These findings demonstrate that sustained N. sativa supplementation enhanced serum globulin response during vvIBDV infection, thus, suggesting its potential as a natural immunostimulant in poultry health management.